2019
DOI: 10.1155/2019/8201639
|View full text |Cite
|
Sign up to set email alerts
|

Osteoid Osteoma in Children Younger than 3 Years of Age

Abstract: We present a case series of four children, younger than 3 years old, with osteoid osteoma of the lower limb. Pain and limping were the main symptoms. With careful clinical examination, we could localize the affected area. Radiological evaluation revealed cortical thickening in 3 children. On MRI examination, we found extensive edema, with normal bony cortices. The central nidus was found in 3 children. CT scan was the most accurate examination which revealed the central nidus with surrounding sclerosis. Bone s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…9 In their series of 4 children under the age of 3 years, Laliotis et al reported the presence of OO in the lesser trochanter of one of the children without the appearance of the central nidus on X rays or MRI. 4 In such instances, where the nidus is obscured by the surrounding sclerosis, CT scan is the modality of choice to help differentiate OO from other lesions such as chronic osteomyelitis with a Brodie's abscess, eosinophilic granuloma, and small round blue cell tumor such as Ewing sarcoma or metastatic neuroblastoma. 5,9 Furthermore, when the central nidus diameter exceeds 1.5 cm, osteochondroma should be considered in the differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 In their series of 4 children under the age of 3 years, Laliotis et al reported the presence of OO in the lesser trochanter of one of the children without the appearance of the central nidus on X rays or MRI. 4 In such instances, where the nidus is obscured by the surrounding sclerosis, CT scan is the modality of choice to help differentiate OO from other lesions such as chronic osteomyelitis with a Brodie's abscess, eosinophilic granuloma, and small round blue cell tumor such as Ewing sarcoma or metastatic neuroblastoma. 5,9 Furthermore, when the central nidus diameter exceeds 1.5 cm, osteochondroma should be considered in the differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases it shows increased uptake in the affected area with the classical double density sign. 4,5,7 This highlights the importance of combination of different imaging modalities when one of them is inconclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction A bone-forming tumor is a benign osteoblastic tumor, accounting for 12% of benign tumors of the bone [4]. It can develop at any age, even before 3 years old [5,6], but its typical presentation is in the second decade, more frequently in boys (two to four times more than girls) [7]. Usually solitary, there have been reports about rare metachronous presentations [8].…”
Section: Bone-forming Tumorsmentioning
confidence: 99%
“…Osteoid osteoma in microscopic examination shows a focus(nidus) build-up with osteoid tissue, surrounded with reactive sclerotic bone with elements of inflammation [9]. Usually, nidus does not exceed 1cm in diameter.…”
Section: Presentation and Diagnosismentioning
confidence: 99%